2010
DOI: 10.1111/j.1365-2664.2010.01865.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways for tree regeneration in anthropogenic savannas: incorporating biotic and abiotic drivers into management schemes

Abstract: Summary1. Oak savannas are biodiversity-rich landscapes allowing sustainable livestock production throughout the world. The long-term persistence of these ecosystems critically depends on the regeneration of the tree layer. Nevertheless, studies addressing the mechanisms involved for conservation planning are of limited value because they tend to focus on single explanatory factors. 2. We evaluated the combined effect of biotic and abiotic factors on recruitment of holm oak Quercus ilex in the Mediterranean sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 29 publications
4
54
2
3
Order By: Relevance
“…Concerning acorn losses, it must be noted that studies based on acorns collected on the ground tend to overestimate acorn damage, as sound acorns are selected by post-dispersal predators . In our study, based on acorns collected from the canopy, the mean attack rate by both insects was 9.40%, that is well below figures reported in comparable studies in holm-oak in dehesas: 18% (Pulido and Díaz, 2005), 58% , and 20% in Pulido et al (2010). On the other hand, Brenneria infested 10.29% of acorns, a figure lower than the 16.30% found by Pulido and Díaz (2005) and 25.60% reported by Vázquez et al (1999).…”
Section: Variation In Acorn Damagecontrasting
confidence: 53%
“…Concerning acorn losses, it must be noted that studies based on acorns collected on the ground tend to overestimate acorn damage, as sound acorns are selected by post-dispersal predators . In our study, based on acorns collected from the canopy, the mean attack rate by both insects was 9.40%, that is well below figures reported in comparable studies in holm-oak in dehesas: 18% (Pulido and Díaz, 2005), 58% , and 20% in Pulido et al (2010). On the other hand, Brenneria infested 10.29% of acorns, a figure lower than the 16.30% found by Pulido and Díaz (2005) and 25.60% reported by Vázquez et al (1999).…”
Section: Variation In Acorn Damagecontrasting
confidence: 53%
“…A long history of human disturbances has strongly influenced ecosystem functioning and species composition in the five Mediterranean regions around the world (Aschmann, 1973;Conacher and Sala, 1998), i.e. California (Stylinski and Allen, 1999;Franklin, 2010), the European Mediterranean Basin (Barbero et al, 1990;Acácio et al, 2009Acácio et al, , 2010Pulido et al, 2010), central Chile Holmgren, 2002;Figueroa et al, 2004;Armesto et al, 2010), southwest South Africa (Brown and Van Staden, 1997;Alston and Richardson, 2006), and southwest Australia (Hobbs and Huenneke, 1992;Dixon et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Other authors, however, have shown the positive effects of encroachment on the functions of silvopastoral systems, such as natural regeneration of trees (Ramírez and Díaz 2008), diversification of animal diet (Patón 2003), erosion control (Lavado et al 2004) and biodiversity conservation (Díaz et al 2003). As a consequence, temporary abandonment and subsequent shrub encroachment have been proposed as a more costeffective tool than artificial plantation to enhance natural recruitment of trees (Pulido et al 2010). This type of dehesa management involves creating a mosaic-type farm and landscape according to a long-term rotation plan, habitual in the past, where forest and encroached plots are mixed with more intensively grazed plots.…”
Section: Introductionmentioning
confidence: 99%